ASSESSING THE INTEGRATION OF GAYS AND LESBIANS INTO THE SOUTH AFRICAN NATIONAL DEFENCE FORCE - Belkin, Aaron; Canaday, Margot (Scientia Militaria - South African Journal of Military Studies, 2011)
During the apartheid era, the South African military maintained a dual policy on homosexuality – prohibited among members of the permanent force, homosexuality was officially tolerated among conscripts. When the regime fell, the new government committed itself to human rights considerations, and after the South African Constitution adopted a provision of non-discrimination on the basis of sexual orientation in 1996, the South African military followed suit. In 1998, the South African National Defence Force (SANDF) implemented the Policy on Equal Opportunity and Affirmative Action that declared that there would no longer be discrimination against gays and lesbians. This article draws together military and government documents, secondary research, press coverage and interviews with individuals with knowledge on this topic to assess the effects of this policy change. The evidence suggests that the integration of gay and lesbian personnel has not had a negative impact on recruitment and retention, morale, unit cohesion or operational effectiveness in the SANDF.